Challenges and opportunities, which BSTU Voenmekh faced with in the context of interuniversity co-operation with University of Nordland - Dashkova, Ekaterina (Universitetet i Nordland, 2014)
Masteroppgave i bedriftsøkonomi - Universitetet i Nordland, 2014